PENGARUH MOTIVASI, DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. KIMIA FARMA PLANT SEMARANG - Huda, Raisha Sukma; Nugraha, Hari Susanta; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
One of the parameters that affect the performance of employees is the motivation and discipline of work, because it is instrumental in improving a work effectiveness. A company can not develop if the productivity of employees also increased in view of the increasing levels of competition in the business world. Motivation and discipline have an influence in increasing produktiitas employees. Because it is, motivation and discipline is an important concern by the company to improve productivity at PT. Kimia Farma Plant. Where the company is engaged in the manufacture of the pharmaceutical industry to produce oil and cosmetics. This research uses explanatory research approach to 48 respondents with sampling techniques Probability Sampling. Sampling techniques (sampling techniques) that provide equal opportunity for each element of the population to be elected as members of the sample. Data collection techniques in this research using interview techniques, questionnaire and literature study. The data obtained were analyzed quantitatively by using analytical tools in the form of the cross table, validity, reliability, simple linear regression, multiple linear regression and hypothesis testing with T test and F test The conclusion from this study is that there is influence between motivation and discipline to work productivity in PT. Kimia Farma Plant Semarang. Influence motivation towards productivity by 58.3%, the effect on the productivity of work disipin of 62.5%. Saran, the company needs to improve the productivity by increasing motivation through direct observation at regular intervals employees and improve discipline by improving the application and perform a closer scrutiny of the violations. But in this case the management should give consideration greater motivation, considering the influence of motivation on productivity is lower than disciplinary influence on productivity.